ANALISIS WACANA KRITIS: MATA NAJWA ON STAGE KEDIRI “MELIHAT INDONESIA - Prihatin, Yulianah; Farida, Deviana (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2019)
Kediri's Talk Show Mata Najwa On Stage, on March 24th 2019 the theme was "Seeing Indonesia". Mata Najwa discusses the small human struggle to become a big person in the country. Because the event was held in Kediri, commonly called the City of Santri, the speakers invited by Najwa Shihab were Indonesian dignitaries from santri. Critical Discourse Analysis is always interesting to study. The researcher will use the Van Dijk analysis model. The results of this discussion are (1) Macro structure contained in the discourse, which is to know Indonesia from boarding schools, how a santri or a small process to become a great person in this country. (2) Superstructure, the opening section opens with an appearance from Nidji's band grub, the introduction opens with a narrative from Najwa Shihab entitled "Seeing Indonesia", then the discussion is displayed video old photo document from JATIM Governor Khofifah Indar Parawansa, MENPORA Imam Nahrowi, Gus Nadzir a students who are permanent lecturers at the University of Australia, and A. Fuadi, the author of the novel Negeri 5 Menara, discussed the challenges faced by Indonesia which included Corruption, Differences, and Reactive attitudes. The closing ceremony ended with messages for the young people from Narasumer. (3) Microstructure, namely the semantic analysis of the questions asked by Najwa Shihab to the speakers